Handbook of Social Psychology 2010
DOI: 10.1002/9780470561119.socpsy001005
|View full text |Cite
|
Sign up to set email alerts
|

Social Cognitive Neuroscience

Abstract: Social cognitive neuroscience is the study of the processes in the human brain that allow people to understand others, understand themselves, and navigate the social world effectively. Social cognitive neuroscience draws on theories and psychological phenomena from across the social sciences including social cognition, political cognition, behavioral economics, and anthropology. The tools used to study these topics are also wide-ranging including functional magnetic resonance imaging (fMRI), positron emission … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
112
1
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(124 citation statements)
references
References 517 publications
4
112
1
3
Order By: Relevance
“…This suggests that our results do not support a specific and exclusive deficit in amygdala function in HFA, but rather a dysfunction in an extended social neural network. Both the insula related to affective processing (for an extended discussion, see Santos et al, 2010), as well as the PCC involved in social evaluative processing (Freeman et al, 2010;Kuzmanovic et al, 2012;Lieberman, 2010;Schiller et al, 2009), represent important nodes in this network.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This suggests that our results do not support a specific and exclusive deficit in amygdala function in HFA, but rather a dysfunction in an extended social neural network. Both the insula related to affective processing (for an extended discussion, see Santos et al, 2010), as well as the PCC involved in social evaluative processing (Freeman et al, 2010;Kuzmanovic et al, 2012;Lieberman, 2010;Schiller et al, 2009), represent important nodes in this network.…”
Section: Discussionmentioning
confidence: 99%
“…The STG has been demonstrated to be specifically associated with identification of physical movement patterns, such as the amount of interactivity between two moving geometrical figures (Schultz et al, 2005), or animacy-inducing movement of objects (Santos et al, 2010;Schultz et al, 2003;Wheatley et al, 2007). These encoded stimulus properties have to be integrated into an evaluative judgment that reflects internal values based on learning and memory, a process that has been specifically associated with the vmPFC (D'Argembeau, 2013; Phan et al, 2004;Zysset et al, 2003) as well as with the PCC (Freeman et al, 2010;Kuzmanovic et al, 2012;Lieberman, 2010;Schiller et al, 2009). These regions may operate in a top-down manner to modulate the unfolding stimulus representation in the STG (Bar et al, 2006), suggesting that the stimulusbased and top-down guided analysis allowing for accurate task performance does not seem to be impaired in HFA (Frith, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This supports the proposal that individuals justify their choice in order to eliminate a threat to the self. On the basis of this literature, we predicted that self-related brain areas such as the ventral MPFC (Kelley et al, 2002) and the dorsal/ventral lateral prefrontal cortex (Lieberman, 2010) would be engaged in postdecisional choice justification. Furthermore, because the public sense of the self involves taking the perspectives of others (Imada and Kitayama, 2010;Kitayama et al, 2004), we anticipated that brain areas implicated in mind reading such as temporal-parietal junction (TPJ, e.g., Saxe and Kanwisher, 2003) and dorsal MPFC (e.g., Gallagher et al, 2000) might also be related to choice justification.…”
Section: Introductionmentioning
confidence: 99%
“…The ability to reflect upon one's current and past experiences, preferences, traits, or abilities is assumed to constitute a hallmark achievement of the human brain (Lieberman, 2010). A large body of research has demonstrated that when people self-reflect they tend to think of themselves as having a more complex personality (Sande, Goethals, & Radloff, 1988), a richer emotional life (Leyens et al, 2000), and adaptive behavioral repertoire (Jones & Nisbett, 1971) compared to other people.…”
mentioning
confidence: 99%